Learning Strategy for Islamic Religious Education (PAI) During the Pandemic (Case Study: SMP Negeri 1 Kembangbahu Lamongan) - Abdul Rahmat Jailani; Bahrissalim Bahrissalim (Universitas Sang Bumi Ruwa Jurai, 2023)
The impact of the Covid-19 pandemic has affected the education system in Indonesia. This of course changes the method of face-to-face learning to distance learning (DL). This study aims to 1) find out the learning strategies of class VII PAI teachers during the Covid 19 pandemic at SMPN 1 Kembangbahu Lamongan; and 2) Knowing the obstacles and solutions faced by teachers in implementing PAI learning strategies for class VII during the Covid 19 pandemic at SMPN 1 Kembangbahu Lamongan. This study uses a descriptive qualitative approach. The subjects of the study were two class VII Islamic Religious Education subject teachers. Data collection techniques: observation, interviews and documentation. The data validation technique uses triangulation techniques. Data analysis techniques are data reduction, data display and conclusion drawing/verification. The results of the study showed that the learning strategy used by teachers was carried out using a distance learning (DL) strategy. Starting from half the number of classes that attend school, then replaced with each grade every week. In addition, there is maximum effort from PAI teachers in carrying out good learning, one of which is by making videos or audio-visual based learning. Google form is also used as a support for technology-based learning and also the application of active learning carried out in schools such as problem solving, and so on. Existing constraints include: 1). insufficient internet quota 2) misuse of internet quota 3) lack of device facilities 4) implementation of different learning methods between online and offline.